Revolutionizing Sustainable Agriculture Through Vertical Farming Innovation - N. Sandeep (International Journal of Intelligent Systems and Applications in Engineering, 2023)
The world population is rapidly increasing and is projected to reach around 9 billion by 2050. This population increase will exert significant strain on existing natural resources and generate a need for enhanced food production. Climate change is a worldwide concern, and agriculture is a contributing factor that requires an effective resolution. Consequently, the Vertical agricultural approach may diminish pollution levels by using 80-95% less water compared to conventional agricultural methods. Moreover, Vertical Farming addresses the escalating food needs of the population while employing less area, water, and chemicals, and cultivating nutritious crops. Nonetheless, food costs will be 5-10% more than those of traditional farming, but this disparity is expected to diminish with additional technological developments. Vertical farms cannot replace conventional farms; rather, they will serve as complementary systems to satisfy future food requirements. It is fiscally prudent, ecologically sustainable, technologically advanced, and, most importantly, health-conscious.